Physico-mechanical properties of GGBS based geopolymer mortar for semi-rigid binder: impact of crumb rubber replacement - Mohd Najmudin Helmi Abu Bakar,; Warid Wazien Ahmad Zailani,; Nazirah Mohd Apandi,; Muhammad Syamim Abdul Mutalif,; Anis Mawaddah Abdul Majid,; Ni Komang Ayu Agustini,; I Nengah Sinarta, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Geopolymer mortar presents a promising alternative to traditional cementitious materials, with the potential to significantly reduce CO2 emissions and support the development of sustainable construction materials. This study investigates the use of waste rubber tyres as a partial sand replacement in rubberised geopolymer mortar, addressing the environmental issue of tyre disposal. Annually, approximately one billion tyres reach the end of their life cycle, with only about 50% being recycled and the rest ending up in landfills. The research evaluates the effects of substituting sand with crumb rubber (CR) at 20%, 40%, 60%, and 80% proportions in geopolymer mortar, focusing on compressive strength, tensile strength, and workability. Results from workability tests revealed that increasing CR content reduced the slump flow by up to 30%. Furthermore, compressive and split tensile strength tests showed a decline in strength with higher CR content. The optimal replacement level of CR was found to be 20%, achieving a compressive strength of 33.35 MPa and a split tensile strength of 3.4 MPa using a GGBS-WCT mix. These findings underscore the potential of utilizing recycled waste materials as aggregate replacements, with significant implications for improving the sustainability and mechanical performance of construction materials.